Primary care medication safety incidents reported to the National Reporting and Learning System (NRLS) - Muhammad, Khalid W. (2021)
Background: Medication-related safety incidents are a significant patient safety issue in healthcare. Despite more than 90% of UK patient healthcare interactions occurring in primary care, there is limited research to understand medication-related safety incidents in this setting. In 2003, the National Reporting and Learning System (NRLS) was created to collate patient safety reports in order to facilitate understanding and learning from incidents across England and Wales. The NRLS is a central reporting system for incidents occurring in healthcare settings and is the most comprehensive incident reporting system in the world. Medication safety incident reports in the NRLS that originate solely from primary care have never been systematically analysed. This thesis aims to describe the nature, range and severity of primary care-based medication incidents reported to the NRLS between 2003 and 2013 in order to identify priority areas for interventions and to make recommendations for improvement. Methods: Quantitative analysis methods, together with some qualitative analysis principles were utilised. A structured process for coding the free-text descriptions of medication incident reports and an exploratory descriptive analysis of the data was performed, followed by thematic analysis. Existing quality improvement interventions that could address the areas were additionally identified and informed the recommendations made. Findings: A total of 83869 records relating to medication incidents in primary care were identified in the NRLS. All incidents classified by the reporter as having an outcome of death, severe harm and moderate harm were reviewed (n = 2556); additionally, 1500 reports resulting in mild harm and 1500 reports resulting in no harm yielded a total of 5556 reports that were reviewed in this study. After excluding non-valid records, 5017 incident reports were identified and analysed. Dispensing incidents were the most frequently reported medication safety issue (n = 3380, 67.4%); followed by administration incidents (n = 760, 15.1%); prescribing and clinical treatment decision incidents (n = 431, 8.6%); adverse drug reactions (n = 220, 4.4%); monitoring incidents (n = 36, 0.7%); and, “other” incidents (n = 190, 3.8%). The majority of the incidents (in which the severity of harm was clear) had a no harm or mild harm outcome (n = 2014/2664, 75%), followed by moderate harm (n = 573/2664, 22%), severe harm (n = 45/2664, 2%) and death (n = 32/2664, 1%). Antidepressants (n = 477) were the most frequently reported medicines to be involved in the incidents overall, followed by opioid analgesics (n = 429), antiepileptics (n = 398), insulins (n = 373) and antithrombotic agents (n = 329). Priority areas identified for improving medication safety in primary care included active failures due to insufficient protocols, workforce and equipment issues, inadequate procedures for implementing medication changes at transfer of care between settings, need for improved staff education and training, medication similarity (look-alike and sound-alike) oversights, lack of adequate or implemented protocols, suboptimal working environment, inadequate administrative practices and insufficient communication of medicines information to patients. Suggested recommendations for improvement included various IT improvements, such as standardising patient electronic healthcare records across all care settings and using automation to allocate staff to a place of work. Conclusions and recommendations: This study has identified priority areas and suggested important recommendations for interventions to improve medication safety. Priority areas included active failures due to insufficient protocols, workforce and equipment; inadequate procedures for implementing medication changes at transfer of care between settings; need for improved staff education and training; medication similarity (look-alike and sound-alike) oversights; lack of adequate or implemented protocols; suboptimal working environment; inadequate administrative practices; and insufficient communication of medicines information to patients. Recommendations included various IT improvements such as standardising patients’ electronic healthcare records across all care settings and using automation to allocate staff to a place of work; direct personalised feedback to healthcare professionals; creation of distraction free zone in a dispensary; and providing medication cards to patients in easy to understand language. Further research on these recommendations should be carried out in order to develop, implement and evaluate them in clinical practice.